Apelin-13 increased food intake with serum ghrelin and leptin levels in male rats - Saral, S.; Alkanat, M.; Sumer, A.; Canpolat, S. (Comenius Univ, 2018)
In this study, we aimed to explain the role of apelin-13 on body weight, food and water intake with serum leptin, ghrelin, neuropeptid Y (NPY) and peptid YY (PYY) levels in male rat. Thirty-two Sprague-Dawley male rats were used for the study. The rats were injected SP (0.9 %) intraperitoneally (i.p) in the control group and 30 (AP30), 100 (AP100) and 300 (AP300) mu g/kg apelin-13 in the study groups, respectively, 10 min before the transition to dark period, for 10 days. During the experimental period, with light and dark periods of food and water intake, body weights were recorded in rats. Rats were euthanized and serum samples were obtained. In serum samples leptin, ghrelin, NPY and PYY levels were measured with specific ELISA kit. Apelin-13 was increased body weights in all three (AP30, AP100 and AP300) groups compared with the control group. AP100 and AP300 groups had increased food intake in the dark and the cumulative period, but in the light period food intake values were not significantly increased (p > 0.05). As for the value of water intake, compared with the control group, all dose of apelin-13 increased water intake during the dark and the cumulative period. There was no significant change in water intake in the light period. On the other hand, compared with the control group, serum leptin levels were found to increase in the groups administered 100 and 300 mu g/kg of apelin-13 (p < 0.05). Ghrelin levels were found high in all groups treated with apelin-13. Serum levels of NPY decreased only in the 300 mu g/kg apelin-13 treated group (p < 0.05). There was no statistically significant change in levels of PYY (p > 0.05). Apelin-13 increases body weight in rats as well as food and water intake (dark and cumulative period). Additionally, ghrelin can mediate the orexigenic effect of apelin-13 in the regulation of food intake (Fig. 4, Ref. 37).
Keywords: apelin-13; food intake; ghrelin; leptin; neuropeptid Y